2019
DOI: 10.7163/gpol.0159
|View full text |Cite
|
Sign up to set email alerts
|

Profile of tourists visiting cultural heritage cities: Comparative study of selected cities in Central Europe

Abstract: The aim of this paper is to explore the profile of tourists visiting Budapest, Prague and Warsaw. These cities were selected for their rich cultural heritage and change in volume of tourism in recent years. Survey data (N = 550) and statistical data on tourist volume were used to show similarities and differences in tourist characteristics in terms of socio-demographics and purpose of travel. The study concluded that most tourists visiting these cities are from Western Europe. The main purpose of travel is ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 27 publications
1
1
1
1
Order By: Relevance
“…The authors concluded that tourists over the age 50 travel to renew their social life, discover new places and acquire knowledge, learn about new cultures, while tourists under the age 18 are motivated by the need to socialize with local people and shop. The results of the research are in line with the conclusions in the study by Tracz and Bajgier-Kowalska (2019). The authors found that younger tourists (up to 29 years old) visit cities to participate in entertainment activities with other people and for education, while the older population (30-59 years old) is motivated by business, visits to relatives, sightseeing, health motives, etc.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The authors concluded that tourists over the age 50 travel to renew their social life, discover new places and acquire knowledge, learn about new cultures, while tourists under the age 18 are motivated by the need to socialize with local people and shop. The results of the research are in line with the conclusions in the study by Tracz and Bajgier-Kowalska (2019). The authors found that younger tourists (up to 29 years old) visit cities to participate in entertainment activities with other people and for education, while the older population (30-59 years old) is motivated by business, visits to relatives, sightseeing, health motives, etc.…”
Section: Discussionsupporting
confidence: 85%
“…Although this topic is explored from different types of destinations and forms of tourism (Battour et al, 2017;Chi et al, 2020;Dryglas, Salamaga, 2018;Garms et al, 2017;Hashim et al, 2019;Rittichainuwat, Rattanaphinanchai, 2015), it is still not sufficiently analyzed from the perspective of urban destinations. (Almeida, Silva, Amoêdo, 2019;Božić et al, 2017b;López-Guzmán et al, 2019;Pulido-Fernández, Cárdenas-García, Carrillo-Hidalgo, 2016;Smith et al, 2022;Tracz, Bajgier-Kowalska, 2019;Zhang, Mao, Qu, 2004), such conclusions were not drawn from this study. A significant number of studies have proven the influence of demographic characteristics on travel motivation (Aziz et al, 2018;Blešić et al, 2014;Carvache-Franco et al, 2020;Moniz et al, 2020;Saayman, Saayman, 2009).…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…The increase in arrivals from China and South Korea was very rapid. The reason was the increasing interest of Asian tourists in Czech cities, cultural and historical monuments, and spas (Tracz and Bajgier-Kowalska, 2019;Tyslová et al 2020). The growing number of direct flights to Korea and China had a positive impact on tourism.…”
Section: Resultsmentioning
confidence: 99%